Immunohistochemical detection of Brucella mellitensis and Coxiella burnetii antigens in formalin-fixed tissues of West African Dwarf goats - Emikpe, Benjamin Obukowho; Mohd Yusoff, Sabri; Ezeasor, Chukwunonso Kenechukwu; Tanko, Polycarp Nwunuji (Internet Medical Publishing, 2013)
Immunohistochemical detection of Brucella mellitensis and Coxiella burnetii antigens in formalin-fixed tissues of West African Dwarf goats. The information on the evidence of Brucella mellitensi and Coxiella burnetti infections or co-infection in goats had been scanty, This investigation reports the immuno-histochemical evidence of Brucella mellitensi and Coxiella burnetti infections in West African dwarf goats. Goats presented for post mortem in the Department of Veterinary Pathology, University of Ibadan were used for this investigation. By simple randomisation, lung, kidney, liver and spleen of fifteen goats were used for this immunohistochemical evaluation using stardard technique. 60% of the goats examined were positive for Brucella mellitensis, 33% were positive for Coxiella burnetti while 7% were positive for both infection. The spleen liver, kidney and lungs were positive for Brucella mellitensis while only the spleen and lungs were positive for Coxiella burnetti. Coxiella burnetti antigens were located in the cytoplasm of macrophages of alveoli of the lung and in the red splenic pulp while Brucella melitensis antigens were located in the cytoplasm of macrophages in the lung, in the red splenic pulp, Kupffer cells of the liver, macrophages in the glomeruli and epithelial cells of cortical tubules. This appears to be the first report of immunohistochemical detection of Brucella and Coxiella antigens in tissues of West African dwarf goats. The presence of these antigens in apparently healthy and pneumonic goats showed the level of risk posed by goats’ meat and meat products in the spread of these zoonotic diseases hence the need for facilities for rapid detection of these diseases.